The Effect of Physical Exercise on Post-COVID-19 Survivors: A Scoping Review - Aini, Nur; Angganita, Rosita Devi; Darojat, Zakiah Wahyu (Universitas Muhammadiyah Yogyakarta, 2024)
Background: Post-COVID-19 survivors or patients show deterioration in respiratory function, physical symptoms, musculoskeletal strength, quality of life (QoL), and psychological problems due to persistent symptoms. These symptoms are associated with mitochondrial dysfunction, reduced antioxidants, and oxidative stress. Physical exercise has been proven to positively affect general and psychological health.Objective: This study intended to explore physical exercise's effect on post-COVID-19 survivors.Methods: Literature in this scoping review was searched from seven databases, including Embase, PubMed, CINAHL, Cochrane, Scopus, Ovid-MEDLINE, and Web of Science. A manual search from Google Scholar and citations from previous meta-analyses were also performed. The keywords are “physical exercise” OR “physical activity” AND “post-COVID” OR “Long COVID.” Studies were included if involving patients with post-COVID diagnosis. However, studies that did not focus on post-COVID-19 focused on respiratory rehabilitation and had no complete data were excluded from this review.Results: 33 studies from 1.909 were included (30 from databases and three citations from previous meta-analyses). Physical activity for post-COVID survivors can improve lung function, exercise capacity, functional capacity, physical symptoms (for instance, pain, fatigue), psychological or QoL, and also biochemical and hematological variables (for example, platelets, red blood cells, white blood cells, hemoglobin, hematocrit, creatinine, and urea).Conclusion: Physical activity programs may represent an important supportive therapy for post-COVID-19 survivors. Therefore, health workers are encouraged to closely monitor respiratory parameters or post-COVID-19 patient symptoms and motivate patients to perform physical exercise.